Effects of an Educational Program on Self-care Behaviors and Its Perceived Benefits and Barriers in Patients with Heart Failure in Tehran - HR Sanati; SS Mazlumi Mahmudabad; MH Baghiani Moghadam; H Nadrian; J Shojafard; MR Asgar Shahi (Tehran University of Medical Sciences, 2009)
Backgrounds and Aim: Self-care behaviors are an important aspect of Heart Failure (HF), management, Educating self-care behaviors to HF patients have to be a part of routine management of HF in hospitals and health care Centers. The aim of this study was to determine the impact of an educational intervention on self-care behaviors and its perceived benefits and barriers in patients with HF in Tehran.Materials and Methods: This is was an interventional study. A Simple sampling was conducted on 180 outpatients (90 intervention group and 90 control group) with HF referring to Shaheed Rajaee Heart Hospital in Tehran to participate in this study. Before and 2 months after implementing the educational program through group discussion, face to face interview, educational movies and pamphlets, a self-prepared questionnaire was completed by the participants. Validity and reliability of the scales were approved. SPSS software was used for the purpose of data entry, manipulation, and analysis. Results: After implementing the educational program, patients' self-care (74.5%) and perceived benefits (19.35%) were significantly increased (P<0.0001) and their perceived barriers (27.76%) were significantly decreased (P<0.0001). After intervention there was no significant difference in these variables in control group.Discussion and Conclusion: In order to design effective educational programs, healthcare professionals and nurses should better understand self-care behaviors in HF patients and their determinants and develop educational interventions. Promoting perceived benefits and barriers of these behaviors are priorities of the program. Healthcare professionals and nurses applying such educational programs can have a more effective role in promoting self-care behaviors and consequently quality of life of HF patients.